Inter-Ethnic Interactions in Urban Public Space: The Malaysian Experience - Hesham Omran Elfartas; Haithem Ahmed Albeera; Jibril Danazimi Jibril (Journal of Pure & Applied Sciences, 2022)
Social interaction entails communal experiences between people during their daily activities. People from different ethnic backgrounds in Malaysia namely the Malays, Chinese and Indians spend their leisure time in an urban square, which offers opportunities for social interaction among three ethnic groups. However, how are public spaces utilised for leisure by people from different multi-ethnic backgrounds? Does the variety of attributes in public spaces attract people from a different background? The current aim of this research sets to establish properties and attributes of urban square characteristics such as the quality of daily activities that contribute to inter-ethnic social interactions among users in urban civic spaces. The study focused on constructing indices on how daily activity attributes, and how to investigate the diversity amongst the three ethnic groups on how the urban public space is perceived. A total of 140 questionnaires were administered to measure how the public square users perceived public space use in Batu Pahat town, Malaysia Peninsular. The analysis was facilitated through analytic tool of the Rasch Model. The study revealed that the Malays use urban squares more than Indians and Chinese. Consequently, this affects the level of the Malays social interaction among others. While on the other hand, for square activities reflecting Chinese and Indian culture makes the urban square less attractive to the Chinese and Indians. It suggests that the environmental attribute quality of the square should be improved to attract social interaction amongst the three ethnic groups.